2002
DOI: 10.1002/j.0022-0337.2002.66.11.tb03602.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do U.S. and Canadian Dental Schools Teach Interpersonal Communication Skills?

Abstract: The status of instruction in interpersonal communication was surveyed in forty U.S and Canadian dental schools. Key faculty members were identified, and syllabi and course descriptions were collected and content-analyzed. The following findings were obtained for responding schools: 1) only one-third of schools had courses specifically focusing on interpersonal communication; 2) more than half of the schools offered these types of courses only during the first two years; 3) the most common topics were communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 33 publications
2
92
0
8
Order By: Relevance
“…To fulfill this aim, the researcher has contacted the course director responsible for teaching communication skills in both universities and has requested the course specification. Course analysis was established based on the following characteristics 1) the extent to which interpersonal communication skills are taught (timing) and where they are taught in the curriculum; 2) what content is taught; 3) what teaching methodology is used; 4) what approaches to evaluation are utilized; and 5) the background of course instructors (19).…”
Section: Methodsmentioning
confidence: 99%
“…To fulfill this aim, the researcher has contacted the course director responsible for teaching communication skills in both universities and has requested the course specification. Course analysis was established based on the following characteristics 1) the extent to which interpersonal communication skills are taught (timing) and where they are taught in the curriculum; 2) what content is taught; 3) what teaching methodology is used; 4) what approaches to evaluation are utilized; and 5) the background of course instructors (19).…”
Section: Methodsmentioning
confidence: 99%
“…Continuous teaching with a gradual increase in complexity has been considered the most effective method of teaching transcultural skills, thus exposure to these concepts in previous undergraduate study may also contribute to differences between the courses [22,23]. Interestingly, a study investigating social and cultural teaching of medical students concluded that the teaching made little to no difference when students began clinical rotations [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous benefits derived from effective communication with patients. These include improved patient satisfaction and compliance (Teutsch 2003), efficient assessment of patient history, and a reduction in patient distress and anxiety (Yoshida, Milgrom, and Coldwell 2002;Jayawardene and LaDuca 2014). Importantly, the outcomes of being an effective communicator include reduced patient complaints ( The limitations of working memory: overload from teaching communication skills with task performance Silverman and Wood (2004) suggest that communication skills are more complicated, therefore more difficult to teach and learn, than the majority of procedural tasks.…”
Section: The Benefits Of Being An Effective Communicator At the Time mentioning
confidence: 99%
“…
More than a decade ago, a limited number of authors (Yoshida, Milgrom, and Coldwell 2002;Kneebone et al 2002; pointed out that it was a rudimentary requirement of all health professionals to be able to communicate with the patient at the time a task was being performed. At this time, some educators believed that the skills to become an effective communicator for clinical task performance were taught during the undergraduate curriculum (Kneebone et al 2002).
…”
mentioning
confidence: 99%